ANALISIS FAKTOR YANG MEMPENGARUHI MINAT KEWIRAUSAHAAN MAHASISWA PENDIDIKAN EKONOMI - Fitria Naifa Nurul Huda; Suci Wulandari; Yulia Novita; Zetri Rahmat (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the factors that influence entrepreneurial interest in Economics students. A descriptive quantitative approach was used, with questionnaires distributed to 80 students. The results indicate that entrepreneurial knowledge, social support, and experience participating in entrepreneurial activities positively influence students' interest in starting a business. On the other hand, limited capital and fear of failure are the main obstacles holding students back from entering the business world. The implications of this study emphasize the need to strengthen the practice-based entrepreneurial climate and provide business mentoring facilities in higher education.